Global Trends Facing Up to a Changing World - Done, Adrian (London : Palgrave Macmillan, 2012)
Looks at the bigger picture, and the future trends that are going to affect the global business world over the next few years. The author analyzes traditional themes such as technology and sustainability but also takes into consideration the effects of developments in other areas such as health, education and demographics.